Fullerene-Intercalated Graphene Nano-Containers — Mechanism of Argon Adsorption and High-Pressure CH and CO Storage Capacities - Artur P. Terzyk; Sylwester Furmaniak; Piotr A. Gauden; Piotr Kowalczyk (Adsorption Science & Technology)
Using GCMC simulations, we discuss the mechanism of argon adsorption onto intercalated graphene nano-containers (NanoBuds). The mechanism is related to the shapes of the high-resolution α S -plots. Next, we have tested the applicability of these materials to the storage of methane and carbon dioxide. We show that intercalation improves the storage, especially in the range of low pressures where the effect of volume does not dominate. The results obtained may be of interest in the design of new carbon materials.